End of Life Decision: We are not Playing God? - Ngow, Harris Abdullah; WMN, Wan Khairina (The Faculty of Medicine, International Islamic University Malaysia, 2013)
Advances in neonatal care now enable more infants to be kept alive despite clear clinical evidence of inevitable or imminent death on a life-support system. It is therefore no longer acceptable to the society that a patient is left to die in the hospital, without any form of treatment or intervention. We report a case of severe birth asphyxia, hypoxic-ischemic encephalopathy, neonatal seizures and left cephalohematoma. In spite of initial successful resuscitation, the infant could not survive until all possible methods of treatment were exhausted. This case illustrates one of many examples of the process involved in dealing with ending of life decision in a condition considered as futile.